2022
DOI: 10.1186/s40694-022-00135-w
|View full text |Cite
|
Sign up to set email alerts
|

Branching and converging pathways in fungal natural product biosynthesis

Abstract: In nature, organic molecules with great structural diversity and complexity are synthesized by utilizing a relatively small number of starting materials. A synthetic strategy adopted by nature is pathway branching, in which a common biosynthetic intermediate is transformed into different end products. A natural product can also be synthesized by the fusion of two or more precursors generated from separate metabolic pathways. This review article summarizes several representative branching and converging pathway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 155 publications
0
14
0
2
Order By: Relevance
“…Many natural product biosynthesis pathways generate similar chemical diversity through branching, for example a multiplicity of xanthanones are derived from chrysophanol via extensive pathway divergence [1b, 18] . The mechanisms that deliver such divergence vary widely, with either a pathway intermediate being accepted by different biosynthetic enzymes or through promiscuous enzymic action [1, 18] . In nodulisporic acid biosynthesis we have revealed that the catalytic promiscuity of NodJ, and resulting mechanistic bifurcation of the pathway, combined with the substrate tolerance of all downstream biosynthetic enzymes delivers diverse chemical output at a very low cost.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Many natural product biosynthesis pathways generate similar chemical diversity through branching, for example a multiplicity of xanthanones are derived from chrysophanol via extensive pathway divergence [1b, 18] . The mechanisms that deliver such divergence vary widely, with either a pathway intermediate being accepted by different biosynthetic enzymes or through promiscuous enzymic action [1, 18] . In nodulisporic acid biosynthesis we have revealed that the catalytic promiscuity of NodJ, and resulting mechanistic bifurcation of the pathway, combined with the substrate tolerance of all downstream biosynthetic enzymes delivers diverse chemical output at a very low cost.…”
Section: Figurementioning
confidence: 99%
“…[1b, 18] The mechanisms that deliver such divergence vary widely, with either a pathway intermediate being accepted by different biosynthetic enzymes or through promiscuous enzymic action. [1,18] In nodulisporic acid biosynthesis we have revealed that the catalytic promiscuity of NodJ, and resulting mechanistic bifurcation of the pathway, combined with the substrate tolerance of all downstream biosynthetic enzymes delivers diverse chemical output at a very low cost. Such interconnected pathways are extremely efficient and have been termed metabolic matrices.…”
mentioning
confidence: 99%
“…Участок белка, образованный 14-161-м аминокислотными остатками, определен как домен, связывающий флавинадениндинуклеотид (FAD), что позволяет предположить, что EasE может работать FAD-зависимо (36,110). Алкалоиды спорыньи лизергинового и пептидного класса образуются из альдегида ханоклавина-I как общего предшественника (122). Окисление ханоклавина-I в альдегид ханоклавина-I в присутствии НАД + катализируется ханоклавин-I-дегидрогеназой, кодируемой геном easD (134).…”
Section: рис 2 искусственно воспроизведенный оптимальный путь биосинт...unclassified
“…Исключающий такие точки оптимизированный путь биосинтеза на примере образования D-лизергиновой кислоте из триптофана приведен на рисунке 2 (9). Накопление промежуточных и конечных продуктов у разных видов и штаммов спорыньи осуществляется неодинаково: образуются клавиновые производные, дигидропроизводные, происходит изомеризация лизергиновой кислоты и синтез лизергин-амидов, пептидных алкалоидов и их эпимеров (34,121,122).…”
unclassified
“…Each individual family of biosynthetic enzymes described above generates myriad natural products; product chemodiversity is even further amplified through the combination of pathways (e.g., TS/PKS, TS/NRPS, or PKS/NRPS) to yield hybrid natural products . Consider fungal meroterpenoids, which are TS/PKS-derived natural products containing terpene and polyketide components. Prominent examples include the meroterpenoid pyripyropene, which is a potent inhibitor of acyl-CoA:cholesterol acyltransferase generated by Aspergillus fumigatus; the antibiotic and immunosuppressant mycophenolic acid, which is generated by Penicillium brevicompactum; and ascofuranone, which is a potential antiparasitic drug produced by Acremonium egyptiacum .…”
Section: Introductionmentioning
confidence: 99%